The Effect of Balancing Funds and Capital Expenditure on The Financial Performance of City Governments in East Java - Revina Ramadina; Sri Trisnaningsih (PT. Maju Malaqbi Makkarana, 2026)
This study aims to examine the effect of balancing funds and capital expenditure on financial performance. A quantitative approach with an associative research design was employed. The population consists of city governments in East Java Province, with a sample of seven cities selected using purposive sampling, resulting in 21 observations during the 2022–2024 period. Data were collected through documentation and analyzed using the SEM-PLS method. The results show that both balancing funds and capital expenditure do not have a significant effect on financial performance. In terms of direction, balancing funds have a negative relationship, while capital expenditure has a positive relationship, although both are statistically insignificant. The coefficient of determination (R² = 0.182) indicates that these variables explain only 18.2% of financial performance, while the remaining 81.8% is influenced by other factors outside the model.